Pembatalan Khitbah Secara Sepihak dalam Perspektif Hukum Islam dan Hukum Sosiologis (Studi Kasus di Desa Parung Panjang Kecamatan Parung Panjang Kabupaten Bogor) - Alfi Ferawati Biseptiana Pasaribu; Usman Musthafa; Yusuf Somawinata (Journal on Education, 2023)
This paper aims to examine the practice of canceling khitbah unilaterally in Parung Panjang Village, Parung Panjang District, Bogor Regency, as well as examining the settlement of canceling khitbah according to Islamic law and sociological law in Parung Panjang Village, Parung Panjang District, Bogor Regency. By using a qualitative approach that is descriptive analysis to obtain complete and objective data. This type of writing is included in the type of field research. From the results of the writing, it can be obtained information that the practice of canceling khitbah unilaterally in Parung Panjang Village, Parung Panjang District, Bogor Regency is a practice of applying marriage proposals in the community, which is still seen as trying to establish certain criteria or reasons. Meanwhile, the settlement of the cancellation of khitbah according to Islamic law and sociological law in Parung Panjang Village, Parung Panjang District, Bogor Regency is Islamic law or sociological law is a basis for cases in order to obtain legal certainty. This case study concludes that the practice of canceling khitbah unilaterally in Parung Panjang Village, Parung Panjang District, Bogor Regency is not wrong in choosing a partner, because marriage is carried out on the basis of mutual love without any coercion from other parties. Meanwhile, the settlement of the cancellation of khitbah according to Islamic law and sociological law in Parung Panjang Village, Parung Panjang District, Bogor Regency is in a family way, because Islam always teaches the best alternative. If in the settlement of the cancellation of the khitbah according to sociological law, that is by way of deliberation